Arterial Occlusive Events in a Patient With Chronic Myeloid Leukemia Treated With Ponatinib - Osamu Imataki; Makiko Uemura (Clinical Case Reports)
ABSTRACT Arterial occlusive events (AOE) are rare adverse event in patients with chronic myeloid leukemia treated with tyrosine kinase inhibitor such as ponatinib. We treated a 47‐year‐old woman with chronic myeloid leukemia. She was failed to achieve optimal molecular response in prior two lines tyrosine kinase inhibitors treatment (dasatinib and bosutinib) for first 30 months. Finally, she was treated with ponatinib and achieve complete molecular remission in 28 months. However, she was suffered from AOE, in bilateral stenosis of the middle cerebral arteries. The patient's responsible vascular lesions of AOE were atypical site rather than usually affected lesions in common arteriosclerosis.